Educational Administration: A Bibliometric Study of Global Knowledge Absorption and Innovation - Patty, Elyakim Nova Supriyedi; iriyani, Sri astuti; Hadi, Heri Sopian; Ria, Reny Refitaningsih Peby; Setiawi, Agustina Purnami (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to map and analyze global trends in the field of Educational Administration, focusing on knowledge absorption and innovation using bibliometric techniques. The method used involves bibliometric analysis to identify publication patterns, research trends, and relationships between subfields of knowledge. Research data were taken from various global academic literature relevant to educational administration and innovation. In collecting data, the researcher uses a literature system as a reference, namely Publish or Perish. In this application, we can select related articles or journal data from Crossref, Google Scholar, Google Scholar Profile, PubMed, Microsoft Academic, Scopus, and Web of Science. Research results show that innovation and knowledge absorption in educational administration are still concentrated in developed countries, while many institutions in developing countries face challenges in adopting these innovations. Furthermore, it was found that international collaboration and technology integration are key factors for the success of educational innovation. This study provides an important contribution to understanding global trends in educational innovation and offers recommendations to strengthen the adoption of innovations through better international collaboration and technology integration.